2010
DOI: 10.1007/s12011-010-8897-5
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10, Copper, Zinc, and Lipid Peroxidation Levels in Serum of Patients with Chronic Obstructive Pulmonary Disease

Abstract: Severity of chronic obstructive pulmonary disease (COPD) exacerbation is associated with increased level of copper (Cu), zinc (Zn), and lipid peroxidation (malodialdehyde, MDA). The aim of this study was to investigate the levels of lipid peroxidation, Coenzyme Q10 (CoQ10), Zn, and Cu in the COPD exacerbations. Forty-five patients with COPD acute exacerbation and 45 healthy smokers as control group were used in the study. Forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) were lower in exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Our finding is supported by a recent study that a decrease in CoQ10 and increase in zinc levels were observed in chronic obstructive pulmonary disease (COPD) patients [31], which probably result from the defense response of organism against zinc-mediated inflammation. There is no direct evidence in relation to zinc and CoQ10 interactions, but our results suggest that CoQ10 may be neuroprotective against zinc-induced mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding is supported by a recent study that a decrease in CoQ10 and increase in zinc levels were observed in chronic obstructive pulmonary disease (COPD) patients [31], which probably result from the defense response of organism against zinc-mediated inflammation. There is no direct evidence in relation to zinc and CoQ10 interactions, but our results suggest that CoQ10 may be neuroprotective against zinc-induced mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, trace element measurement can enable detection of more disorders of the airway and also provide valuable information about pulmonary inflammation in COPD-like conditions. 27 Telomerase is a unique polymerase, and it synthesizes telomeric repeats. 28,29 There are 2 core components of telomerase: the catalytic reverse transcriptase and the RNA component.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, free radicals effects are connected with a formation of atherosclerotic lesions. In body fluids (blood, urine) the increased levels of peroxidation end-products (MDA, 4-HNE, isoprostanes) are present [26,27]. The lipid peroxidation by free radicals occurs in three stages: initiation, propagation and termination [2,26].…”
Section: Introductionmentioning
confidence: 99%